An introduction to DNA microarrays for gene expression analysis - Karakach, Tobias K.; Flight, Robert M.; Douglas, Susan E.; Wentzell, Peter D. (Chemometrics and intelligent laboratory systems, 2010)
This tutorial presents a basic introduction to DNA microarrays as employed for gene expression analysis, approaching the subject from a chemometrics perspective. The emphasis is on describing the nature of the measurement process, from the platforms used to a few of the standard higher-level data analysis tools employed. Topics include experimental design, detection, image processing, measurement errors, ratio calculation, background correction, normalization, and higher-level data processing. The objective is to present the chemometrician with as clear a picture as possible of an evolving technology so that the strengths and limitations of DNA microarrays are appreciated. Although the focus is primarily on spotted, two-color microarrays, a significant discussion of single-channel, lithographic arrays is also included.